Marine-Derived Matairesinol: A Potential Antimicrobial Agent Against Klebsiella pneumoniae from Sponge-Associated Trichoderma longibrachiatum - Sri Sedjati; Ambariyanto Ambariyanto; Agus Trianto; Gunawan W. Santosa; Muhammad S. Bahry; Ayunda Ainun Nisa (ILMU KELAUTAN: Indonesian Journal of Marine Sciences, 2026)
The fungus Trichoderma sp., which is associated with marine sponges, produces various antibacterial compounds that can be used as lead compounds for new antibiotics. The ethyl acetate extract of the sponge-associated fungus Trichoderma longibrachiatum contains an active compound that inhibits the growth of Klebsiella pneumoniae. This study aimed to identify the sponge host and determine the active compound produced by this fungus with anti-K. pneumoniae activity. This study began with a sample of fungal cultures and the identification of the host sponge. The extract samples were obtained using a partition method between methanol and ethyl acetate. Determination of antibacterial compounds in ethyl acetate extracts using disc diffusion and bioautography. Active compounds were identified using Liquid Chromatography-Tandem Mass Spectrometry (LC-MS/MS) and Nuclear Magnetic Resonance Spectroscopy (NMR). The results showed that the host sponge of T. longibrachiatum is Axinella sp. The ethyl acetate extract exhibited antibacterial activity against K. pneumoniae, with inhibition zones of 10.12 and 14.45 mm at doses of 250 and 500 μg discs-1,respectively. The bioautography test revealed that the active fraction had a retardation factor (Rf) of 0.14. The active compound was isolated and anti-K. pneumoniae was identified as matairesinol (C20H22O6), also known as (3R,4R)-3,4-bis[ (4-hydroxy-3-methoxyphenyl) methyl]oxolan-2-one). Matairesinol is a polyphenol from the lignan group with a gamma (γ)-lactone ring. The isolation of matairesinol as an active antibacterial compound against K. pneumoniae provides valuable insights into the potential of marine-derived fungi as a source of novel antimicrobial agents.